In vitro anti-prostate cancer efficacy and phytochemical composition of the dichloromethane and ethyl acetate leaf extracts of Vitex doniana (sweet) - Moriasi, Gervason; Ngugi, Mathew; Mwitari, Peter; Omwenga, George (Frontiers in Pharmacology, 2024)
Background Prostate cancer is a significant global health concern, particularly among ageing male populations, with a disproportionately higher burden in sub-Saharan Africa. Conventional treatments, though effective, are costly and cause devastating side effects which limit their clinical benefits. Hence, this study evaluated the in vitro antiprostate cancer properties and secondary metabolites of dichloromethane and ethyl acetate lead extracts of Vitex doniana to explore safer and efficacious natural alternatives based on ethnomedicinal claims. Methods Phytochemical profiling was conducted using gas chromatography-mass spectrometry (GC-MS) analysis to identify secondary metabolites in the extracts. The cytotoxic effects of the extracts were determined through the MTT assay using Vero CCL-81 cells and DU-145 cells. The expression profile of the selected genes (ar, bcl2, caspase-3, cdk1, and p53) in DU-145 cells treated with the study extracts was investigated using RT-qPCR. Results GC-MS analysis revealed 10 secondary metabolites in the dichloromethane extract and 27 secondary metabolites in the ethyl acetate extract of V. doniana leaves, with the majority being sesquiterpenes, diterpenoids, and phytosterols. The dichloromethane and ethyl acetate leaf extracts of V. doniana exhibited low cytotoxicity against normal mammalian epithelial cells (Vero CCL-81), with CC50 values of 1,238.85 μg/mL and 964.81 μg/mL, respectively. Besides, the ethyl acetate leaf extract of the studied plant demonstrated potent anti-prostate cancer activity against DU-145 cells, with an IC50 of 35.68 μg/mL and a high selectivity index (SI) of 27.04. Likewise, the dichloromethane leaf extract of this plant displayed cytotoxic effects (IC50: 287.01 μg/mL) and a selectivity index of 4.32. The reference drug (Doxorubicin) showed a higher toxicity against Vero CCL-81(IC50: 0.41 μg/mL) and DU-145 (IC50: 0.28 μg/mL) cells and a lower selectivity index of 1.46. The DU-145 cells treated with the studied plant extracts exhibited notable upregulation of ar and bcl2, and normalization of caspase 3, cdk1 and p53 expression. Conclusion The studied plant extracts possess in vitro anti-prostate cancer properties and could be promising candidates for further preclinical studies aimed at developing novel botanical-based therapies for the management of prostate cancer.